A Hybrid Chaotic Image Encryption Scheme Bas~d on S-Box and Ciphertext Feedback - MUHAMMAD ASIM (2007)
The fascinating developments in digital image processing and network communications during the past decade have created a great demand for real-time secure image transmission over the internet and through wireless networks. Due to some intrinsic features of images, such as bulk data capacity and high correlation among pixels, traditional encryption algorithms such as IDEA, DES and AES are not suitable for practical image encryption, especially for real time applications. In order to meet these challenges, a number of schemes have been proposed for encryption of digital images, making use of chaotic dynamical systems. The objective of the work undertaken in this thesis is two-fold - firstly to evaluate the security of a few representative chaotic ciphers by performing the cryptanalysis on them and secondly, to design an appropriate cipher that would fulfill the needs for both security and speed. The cryptanalysis is performed on two recently proposed chaotic ciphers by Pareek eta!. in [Pareek et a!., 2005] and [Pareek et a!., 2006]. The first cipher is a generic chaotic block cipher. It is shown that the proposed cipher is insecure against differential and knownplaintext attacks. We also show that the key space size of the proposed cipher is less than what is claimed by the authors. The second cipher of Pareek et a!. is a complete image encryption scheme. This scheme is also shown insecure against the differential attack in the thesis. It is also shown suffering from a few security defects and, therefore, is not suitable for real time secure encryption of digital images. In this work, a complete image encryption scheme - Hybrid Chaotic Image Encryption Scheme (HyChiES) is designed. HyChiES is based on a cryptosystem consisting of multiple piecewise linear chaotic maps (m-PLCMs), a generalized logistic map, AES S-box and ciphertext feedback. The analysis of the HyChiES shows that it is extremely sensitive to changes in pixels and, therefore, has an avalanche effect - a highly desirable property for any cipher. As a result, HyChiES randomizes plain images very effectively